(√х-х+2)(√х-3)(√х+3)=0

0 голосов
53 просмотров

(√х-х+2)(√х-3)(√х+3)=0


Алгебра (1.7k баллов) | 53 просмотров
0

еще бы корни правильно поставил, то 100 % правильно бы решил.

Дан 1 ответ
0 голосов

(\sqrt{x} -x+2)*(\sqrt{x} -3)* (\sqrt{x} +3) = 0

\sqrt{x} - x + 2 = 0

\sqrt{x} -3 =0

\sqrt{x} +3 = 0

x = 1

x = 4

x = 9

x ∈ ∅

x = 1

x = 4

x = 9

(\sqrt{1} -1+2) * (\sqrt{1} -3) * (\sqrt{1} +3) = 0

(\sqrt{4} -4 +2) * (\sqrt{4} -3) * (\sqrt{4}+3) = 0

(\sqrt{9}-9+2) * (\sqrt{9} -3) * (\sqrt{9} +3) = 0

- 16 = 0

0 = 0

0 = 0

x ≠ 1

x = 4

x = 9

x₁ = 4, x₂ = 9


(654k баллов)